Modelado y cálculo de parámetros de campos fotovoltaicos en condiciones climáticas irregulares - Bastidas Rodríguez, Juan David; Ramos-Paja, Carlos Andrés; Franco Mejia, Edison (Ingeniería, 2012)
In this paper, a model for photovoltaic (PV) fields and a procedure for calculating the parameters of the modules of a string (a group of PV modules connected in series) are presented. The proposed model considers the series and parallel resistors of the photovoltaic modules, the bypass diodes as ideal switches and represents the blocking diodes with the Shockley equation, which allow to express the string voltage as an explicit function of the load current by using the LambertW function; in this way it is possible to construct one equation per string for calculating its current for a given voltage. That procedure is repeated for each string and the current of the field is evaluated by adding the currents of all strings. The parameter calculation procedure evaluates the voltage and current of each active module from the current and voltage of the string and fits the current equation of a module to the experimental data. The accuracy of the proposed model was tested experimentally with a string of two modules obtaining an accuracy improvement near to 50%.